Processing and interpretation of vintage 2D marine seismic data from the outer Hanö Bay area, Baltic Sea - Sopher, D.; Juhlin, Christopher (2013)
A grid of previously unpublished, vintage 2D marine seismic lines has been processed and interpreted to the east of Hanö Bay, SW Baltic Sea. The 3200km2 study area lies on the transition between the Hanö Bay Basin to the West and Baltic Synelcise to the East, NE of the Tornquist intra shield tectonic zone.Data from the NA79, NA80 and RW84 surveys were selected for this study from the extensive Oljeprospektering AB (OPAB) Baltic Sea dataset. New processing workflows have been developed for the data which focus on suppressing two significant forms of noise, namely multiple and side scattered noise. Deconvolution in the tau-p domain, parabolic radon demultiple and post stack deconvolution are shown to be effective at attenuating multiple noise, while FK filtering in shot and receiver gathers is effective at removing side scattered noise.The newly processed data were interpreted and a series of maps detailing the structure of the basement, Cambrian and Silurian/Paleozoic horizons were constructed. These maps differ significantly to previously published interpretations of the area. Within the study area, a region of significant Late Carboniferous/Early Permian transtensional faulting and Late Cretaceous inversion is mapped in detail. This structure would have exhibited normal offsets of up to 600. m before inversion with later inverted displacements of up to approximately 200. m in places. This feature appears to extend some 20. km to the SW of the study area to the major fault bounding the Christiansø High. Based on the seismic interpretation, the area appears to have had a similar overall geological history as the adjacent Tornquist Zone to the SW. © 2013 The Authors.